Click JAHAs: Conformationally restricted ferrocene-based histone deacetylase inhibitors - Spencer, J; Amin, J; Boddiboyena, R; Packham, G; Cavell, B; Syed Alwi, S; Paranal, R; Heightman, T; Wang, M; Marsden, B; Coxhead, P; Guille, M; et al. (2012)
A small library of ferrocene-based 1,2,3-triazole-containing hydroxamic acids has been synthesised employing click chemistry: 7-(4-ferrocenyl-1H-1,2,3- triazol-1-yl)-N-hydroxyheptanamide, 4b, containing the 1,2,3-triazole moiety adjacent to the ferrocene group, displayed excellent HDAC inhibition and activity in cells, inhibiting the deacetylation of tubulin as well as inducing cell cycle arrest. This journal is © The Royal Society of Chemistry.